2017
DOI: 10.1128/aem.02990-16
|View full text |Cite
|
Sign up to set email alerts
|

Lentinula edodes Genome Survey and Postharvest Transcriptome Analysis

Abstract: Lentinula edodes is a popular, cultivated edible and medicinal mushroom. Lentinula edodes is susceptible to postharvest problems, such as gill browning, fruiting body softening, and lentinan degradation. We constructed a de novo assembly draft genome sequence and performed gene prediction for Lentinula edodes. De novo assembly was carried out using short reads from paired-end and mate-paired libraries and by using long reads by PacBio, resulting in a contig number of 1,951 and an N 50 of 1 Mb. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 85 publications
(105 reference statements)
9
67
0
1
Order By: Relevance
“…Several putatively FCW‐active CAZymes (Fig. S4), were developmentally regulated, including chitin‐ and glucan‐active glycoside hyrolase (GH) and glycosyl transferase (GT) families, carbohydrate‐binding modules, carbohydrate esterases, AA1 multicopper oxidases and AA9 lytic polysaccharide monooxygenases, reinforcing the view that cell wall remodeling is a fundamental mechanism in fruiting body development (Sakamoto et al ., , , ; Busch & Braus, ; Martin et al ., ; Buser et al ., ; Ohm et al ., ; Konno & Sakamoto, ; Krizsán et al ., ). Two of 10 members of the Kre9/Knh1 family were developmentally regulated.…”
Section: Resultsmentioning
confidence: 98%
“…Several putatively FCW‐active CAZymes (Fig. S4), were developmentally regulated, including chitin‐ and glucan‐active glycoside hyrolase (GH) and glycosyl transferase (GT) families, carbohydrate‐binding modules, carbohydrate esterases, AA1 multicopper oxidases and AA9 lytic polysaccharide monooxygenases, reinforcing the view that cell wall remodeling is a fundamental mechanism in fruiting body development (Sakamoto et al ., , , ; Busch & Braus, ; Martin et al ., ; Buser et al ., ; Ohm et al ., ; Konno & Sakamoto, ; Krizsán et al ., ). Two of 10 members of the Kre9/Knh1 family were developmentally regulated.…”
Section: Resultsmentioning
confidence: 98%
“…Vetchinkina et al (52) reported that chi1 showed a higher transcription level at the mycelial mat, primordium, and fruiting body stages of L. edodes than at vegetative mycelium. Sakamoto et al (51) found that the transcription levels of chi1 and chi3, as well as chitinase activity, increased in postharvest fruiting bodies of L. edodes. These transcriptome analyses indicated that the homologs of C. cinerea chitinase ChiE1 and ChiIII are important for cell wall degradation in L. edodes.…”
Section: Figmentioning
confidence: 99%
“…The orthologs of FvCPC2 were highly conserved and widespread in different edible mushrooms. Most of the FvCPC2 ortholog encoding genes specifically expressed during fruiting body development in mushroom species (Yu et al, 2012;Zhang et al, 2015;Sakamoto et al, 2017). Thus, genes encoding FvCPC2 orthologs in other mushroom species may also have potential application in breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Although orthologs of CPC-2 have been predicted in the genomes of several mushrooms, including model mushroom species (C. cinerea and S. commune) and cultivated mushrooms (Flammulina velutipes, Volvariella volvacea, Pleurotus ostreatus, Ganoderma lucidum, and Lentinus edodes) (Ohm et al, 2010;Stajich et al, 2010;Grigoriev et al, 2012;Bao et al, 2013;Park et al, 2014;Riley et al, 2014;Sakamoto et al, 2017), none of them has been functionally characterized. Similarly as that cpc-2 is up-regulated after crossing in N. crassa (Lehr et al, 2014), CPC-2 orthologs have an increased expression during fruiting body development in many mushroom species (Ohm et al, 2010;Yu et al, 2012;Cheng et al, 2013;Liu et al, 2015;Zhang et al, 2015;Sakamoto et al, 2017), suggesting that CPC-2 orthologs are likely involved in fruiting body development in these mushroom species. If it is true, CPC-2 ortholog encoding genes have potential to be a new group of reference genes for mushroom breeding.…”
Section: Introductionmentioning
confidence: 99%